From monocentric ideal to polycentric pragmatism in the Syr Darya: searching for second best approaches - Wegerich, Kai; Kazbekov, Jusipbek S.; Lautze, Jonathan F.; Platonov, Alexander; Yakubov, Murat (Inderscience Publishers, 2012)
While best practice in water management typically calls for the use of a basin-level approach, specific guidance in the absence of basin-level management is fairly scant. This paper reviews the experience of the Syr Darya basin to identify insights related to second best practices for water management at scales below the basin level. This paper first presents the causes for the disintegration of river basin management within the Syr Darya, which include both changes in operation of the Toktogul reservoir and rising water demands due to shifts in agricultural production and land ownership. Focus is then devoted specifically to small transboundary tributaries, where bottom-up cooperation has continued or reemerged in recent times. This paper concludes by highlighting the limitations to singular focus on sub-basins and tributaries, suggesting a balance between more intense cooperation and water control on tributaries and a loose overarching framework at the basin level.